2018
DOI: 10.3390/w10020098
|View full text |Cite
|
Sign up to set email alerts
|

A Paradigm Shift in Water Quality Governance in a Transitional Context: A Critical Study about the Empowerment of Local Governance in Georgia

Abstract: Abstract:The management of water quality is an important part of natural resource governance. Assurance of water quality therefore requires formulation of the regulatory framework and institutional process. Water quality-related problems and their management are mainly recognized as local responsibilities in Integrated Water Resources Management (IWRM). The politics of environmental policy-making should consider the political economic dynamics and socio-ecological patterns. Decentralization by providing more p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 75 publications
(67 reference statements)
0
35
0
5
Order By: Relevance
“…Georgia is in a phase of transforming their water resource management systems so as to comply with the framework of the WFD. People's participation and a consideration of the people's concerns regarding water quality is therefore an essential governance element [36]. Thus, this study concludes by briefly explaining the policy implications of analyzing risk perceptions in the context of water quality.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Georgia is in a phase of transforming their water resource management systems so as to comply with the framework of the WFD. People's participation and a consideration of the people's concerns regarding water quality is therefore an essential governance element [36]. Thus, this study concludes by briefly explaining the policy implications of analyzing risk perceptions in the context of water quality.…”
Section: Introductionmentioning
confidence: 94%
“…An analysis of the public risk perception and the consideration of their concerns over water quality have been identified as crucial factors for an operative water quality governance system [36,37,44]. Within this survey, we also asked about the existing mechanisms for farmers to participate in water quality governance.…”
Section: Policy Implications Of Farmers' Risk Perception Analysis Formentioning
confidence: 99%
“…Participatory structures of different sizes and forms in France were frequently introduced at the hydrological scale without fully adapting them to political structure [51]. After examining the case of Georgia, a transitional country, Withanachchi et al (2018) found that granting a greater power to local governments can bring more financial, political, and social advantages to local water institutions regarding water quality issues since the local governments are the proximate level of water pollution control [52]. The degree of softness and the magnitude of scale jumping follow the specific logic of the division of powers among the governments at various levels.…”
Section: "Soft" Bureaucracy At Lower Levelsmentioning
confidence: 99%
“…However, the success of sustainable development is determined by potential relationships among the involved competing actors with natural resources across the entire levels and management structures in different governance scales. To meet competing socioeconomic demands, natural resources are governed, while environmental sustainability is also given priority [25].…”
Section: Governance Systems In Natural Resource Managementmentioning
confidence: 99%